Kisspeptin/Kisspeptin Receptor System in the Ovary - Hu, Kai-Lun; Zhao, Hongcui; Chang, Hsun-Ming; Yu, Yang; Qiao, Jie (Frontiers in Endocrinology, 2018)
Kisspeptins are a family of neuropeptides that are critical for initiating puberty and regulating ovulation in sexually mature females via the central control of the hypothalamic–pituitary–gonadal axis. Recent studies have shown that kisspeptin and its receptor kisspeptin receptor (KISS1R) are expressed in the mammalian ovary. Convincing evidence indicates that kisspeptins can activate a wide variety of signals via its binding to KISS1R. Experimental data gathered recently suggest a putative role of kisspeptin signaling in the direct control of ovarian function, including follicular development, oocyte maturation, steroidogenesis, and ovulation. Dysregulation or naturally occurring mutations of the kisspeptin/KISS1R system may negatively affect the ovarian function, leading to reproductive pathology or female infertility. A comprehensive understanding of the expression, actions, and underlying molecular mechanisms of this system in the human ovary is essential for novel approaches to therapeutic and diagnostic interventions in reproductive diseases and infertility.